Service Quality and its Impact on Customer Satisfaction and Customer Loyalty in Supermarkets/Grocery Stores in TRNC - Mamedova, Kamilya (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
The problem of quality in service trade is constantly worried by buyers and sellers for quite natural reasons. Quality is one of the fundamental characteristics of the goods, which has a decisive influence on consumer demand and competitiveness. In addition, the quality of trade services is a tool in the competition. Therefore, in the competitive market of great importance given to the quality of trade services, since it determines the effective trading activity of any enterprise, the main indicator of which is the amount of profit. The aim of the study is to identify the amount of the quality service provided by supermarkets/grocery stores and its impact on the customer satisfaction and customer loyalty in Turkish Republic of Northern Cyprus. The main objectives of this study are to analyze the consumer behavior and preferences of visitors’ retailers of TRNC, as well as to develop a list of recommendations of consulting for a variety of retailers to meet the requirements of their customers, the ratio respect to the quality of their services. The data will be collected from different supermarkets and grocery stores in Northern Cyprus by distributing questionnaires. Keywords: service quality, customer satisfaction, customer loyalty, supermarkets/grocery stores in TRNC.

ÖZ: Servis ticaretinin kalite problemi oldukça doğal nedenlerle alıcı ve satıcı hakkında sürekli endişe duyuyor. Kalite - malların temel özelliklerinden biridir ve tüketici talebi ve rekabet gücü üzerinde belirleyici bir etkiye sahiptir. Ek olarak, ticari hizmetlerin kalitesi bir rekabet aracıdır. Bu nedenle, bugünkü rekabetçi pazarda ticaret hizmetlerinin kalitesine verilen büyük önem herhangi bir işletmenin etkili ticaret aktivitesidir ve kar miktarının ana göstergesidir. Bu çalışmanın amacı Kuzey Kıbrıs Türk Cumhuriyeti'nin süpermarketler / marketlerinde hizmet kalitesinin miktarını, ve müşteri memnuniyeti ve müşteri sadakati üzerindeki etkisini tespit etmektir. Bu çalışmanın temel amacı, KKTC perakendecilerin tüketici davranışını ve tercihlerini analiz etmek ve müşterilerinin ihtiyaçlarını karşılamak için perakendecilerin çeşitli danışmanlık listeleri geliştirmektir. Veriler nicel anket yoluyla Kuzey Kıbrıs'taki farklı süpermarketler ve marketlerden tahsil edilecektir. Anahtar Kelimeler: t-testi, hızmet kalitesi, musteri memnuniyeti, KKTC
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2016. Supervisor: Prof. Dr. Mustafa Tümer.
Keywords: Business Administration; Marketing Management; Service Quality-Customer Satisfaction-Customer Loyalty-Supermarkets-Cyprus, North; Service quality; customer satisfaction; customer loyalty; supermarkets/grocery stores in TRNC